Hedgehog Autoprocessing: From Structural Mechanisms to Drug Discovery - Kandel, Nabin; Wang, Chunyu (Frontiers in Molecular Biosciences, 2022)
Hedgehog (Hh) signaling plays pivotal roles in embryonic development. In adults, Hh signaling is mostly turned off but its abnormal activation is involved in many types of cancer. Hh signaling is initiated by the Hh ligand, generated from the Hh precursor by a specialized autocatalytic process called Hh autoprocessing. The Hh precursor consists of an N-terminal signaling domain (HhN) and a C-terminal autoprocessing domain (HhC). During Hh autoprocessing, the precursor is cleaved between N- and C-terminal domain followed by the covalent ligation of cholesterol to the last residue of HhN, which subsequently leads to the generation of Hh ligand for Hh signaling. Hh autoprocessing is at the origin of Hh signaling and precedes all downstream signaling events. Mutations in the catalytic residues in HhC can lead to congenital defects such as holoprosencephaly (HPE). The aim of this review is to provide an in-depth summary of the progresses and challenges towards an atomic level understanding of the structural mechanisms of Hh autoprocessing. We also discuss drug discovery efforts to inhibit Hh autoprocessing as a new direction in cancer therapy.